HOW ARE PARTNERSHIPS BETWEEN PRME SIGNATORIES AND BUSINESSES USED IN THE EMBEDDING OF SUSTAINABILITY INTO BUSINESS SCHOOLS AND HIGHER EDUCATION INSTITUTIONS? - Body, Patrick (2018)
The Principles for Responsible Management Education (PRME) is a UN backed initiative that aims to embed sustainability into Business Schools and Higher Education Institutions (HEIs). Signatories adhere to the six published principles and in doing so report on their actions at the end of each two-year cycle. This work focusses specifically on the use of cross-sector partnerships (Principle 5) and their reporting in this endeavour. Placing itself in the partnership literature and drawing from Institutional Theory, Organisational Learning Theory and Critical Theories, this research uses the data from the Sharing Information on Progress (SIP) reports of 59 PRME signatories in the United Kingdom. The research finds very little evidence of value creation or embedding of sustainability within these organisations as reported in the SIPs and identifies limitations in the supporting information for the reporting process that may contribute to suboptimal reporting. The paper makes recommendations for improving the reporting process, refining the PRME definition and suggestions for future research.